(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
Sinoxylon unidentatum (Fabricius) (= S. conigerum Gerstacker) was found infesting wood pallets used to import tea from Sri Lanka. The tea arrived in Italy in June 2009. The beetles completed the development in the warehouse and spread the infestation to other pallets. S. unidentatum was previously intercepted in Italy but this is the first time it has been reported to be able to complete the development and to spread the infestation in an indoor site.